Coexistence of Hermansky-Pudlak syndrome and JAK2V617F-positive essential thrombocythemia. (2nd January 2019) - Eskazan, Tugce; Erturkuner, Salime Pelin; Isildar, Basak; Eskazan, Ahmet Emre; Ar, Muhlis Cem; Atay, Kadri; Baslar, Zafer; Tasyurekli, Mustafa
ABSTRACT: Hermansky-Pudlak syndrome (HPS) is an autosomal recessive disorder consisting of oculocutaneous albinism, platelet storage pool deficiency, and lysosomal accumulation of ceroid lipofuscin. The storage pool deficiency of HPS is associated with the lack of dense bodies in the platelets, resulting in impaired response in the secondary phase of aggregation. Patients with HPS have normal coagulation tests; however, their bleeding time is usually prolonged despite normal or increased platelet counts. Essential thrombocythemia (ET) is an uncommon condition, with an incidence of approximately 1.1 per 100, 000/year, and it is the most common cause of primary thrombocytosis. JAK2 V617F positivity can be observed in approximately half of the patients with ET. Bleeding events in ET have usually been associated with acquired von Willebrand syndrome paradoxically occurring when the platelet counts are extremely high. We, herein, present a case with bleeding diathesis diagnosed as having both HPS and JAK2 V617F -positive ET.